2006
DOI: 10.1007/s11098-006-9047-y
|View full text |Cite
|
Sign up to set email alerts
|

The folk strike back; or, why you didn’t do it intentionally, though it was bad and you knew it

Abstract: Recent and puzzling experimental results suggest that people's judgments as to whether or not an action was performed intentionally are sensitive to moral considerations. In this paper, we outline these results and evaluate two accounts which purport to explain them. We then describe a recent experiment that allegedly vindicates one of these accounts and present our own findings to show that it fails to do so. Finally, we present additional data suggesting no such vindication could be in the offing and that, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 18 publications
8
46
1
1
Order By: Relevance
“…This interpretation fits with two aspects of the current results: (1) the timing of the effect of fairness in the RTPJ, which emerged only after moral judgment and (2) the correlation between the magnitude of the effect in the RTPJ and the earlier investment during the Game. Both the S-E-E and the current fMRI results may therefore suggest a common psychological mechanism for post hoc blame justification (Nadelhoffer, 2004a(Nadelhoffer, , 2004bPhelan & Sarkissian, 2008).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This interpretation fits with two aspects of the current results: (1) the timing of the effect of fairness in the RTPJ, which emerged only after moral judgment and (2) the correlation between the magnitude of the effect in the RTPJ and the earlier investment during the Game. Both the S-E-E and the current fMRI results may therefore suggest a common psychological mechanism for post hoc blame justification (Nadelhoffer, 2004a(Nadelhoffer, , 2004bPhelan & Sarkissian, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…We hypothesized that one key source of such information would be the observer's impressions of the actor's prior record, based on personal experience and/or knowledge of the actor's offense history (Nadelhoffer, 2004a(Nadelhoffer, , 2004bPhelan & Sarkissian, 2008;Pizarro et al, 2006;Woolfolk et al, 2006). The behavioural results of the current experiment support this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…Presumably, the restructuring plan will lead to a long-term increase in profits. Indeed, when Phelan and Sarkissian (2008) that decreasing sales was bad, 94.5% of participants indicated that Susan deserved neither praise nor blame, and only 14% thought that decreasing sales was bad. These data contrast sharply with the praise and blame ratings obtained by Knobe (2003a) for ENVIRONMENT.…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies have examined neutral outcomes in assessments of the side-effect effect (Knobe and Mendlow, 2004;Phelan and Sarkissian, 2008). Outcomes in the present study that were considered neutral were that the target individual in the story would fall asleep, tap her foot, or see a frog for the first time.…”
Section: Responses To Neutral Outcomesmentioning
confidence: 96%